4차 산업혁명시대에 따른 전문대학 교양교육의 개선 방향 연구 - 최미숙(Choi, Mi-Sook) (교양교육연구, 2017)
본 연구는 4차 산업혁명시대를 맞이하여 초융합과 초연결의 급격한 변화 속에 세계적 수준의 창조적 직업교육을 선도하기 위한 연구로 4차 산업혁명시대에 따른 전문대학 교양교육의 개선 방향을 제시 하는데 그 목적이 있다. 연구대상으로는 1차 설문조사에 W보건대학교 교수요원 100명을 선정하였고, 2차 표적집단인터뷰(focus group interview)에 6명을 연구대상으로 선정하였다. 연구절차는 W보건대학교 교수요원들을 대상으로 교양교육에 관한 인식 및 요구정도와 만족도에 관한 설문조사를 실시하기 위하여 생명윤리위원회의 연구계획서 심의 승인을 받은 후 1차 설문조사로 양적연구를 진행하였다. 이어 그 결과를 토대로 교수요원들이 인식하고 있는 교양교육의 본질적 목적과 개선방향에 대한 실질적인 내면의 소리를 조사하고자 2차 표적집단인터뷰(focus group interview)를 실시하여 질적연구를 진행하였다. 그 결과 4차 산업혁명 시대에 따른 전문대학 교양교육의 개선 방향을 다음 3가지로 제시한다. 첫째, 전공교과와 교양교과를 연계한 우수콘텐츠 개발로 교과간 통합과 융합으로 통찰력을 갖출 수 있는 기초역량 강화를 넘어 삶과 연결하는 방향으로 통합적 교양교육의 본질적 목적 실현을 위한 교양교육으로 개선되어야한다. 둘째, 4차 산업혁명을 선도할 창의·융합적 인재육성 관련 교양교육과정 연구개발로 실천적 지식을 포함한 생활문화 전반에 대한 넓은 안목과 지견을 습득할 수 있도록 하는 방향으로 인간의 잠재가능성 향상과 사회적 실천과 연결된 다양한 지식을 줄 수 있는 유기적 교양교육과정으로 개선되어야 한다. 셋째, K-MOOC를 활용한 교양교육 확대실시로 다양한 교과목을 구성하여 대학의 경쟁력 강화와 시대적·사회적 요구에 부합한 방향으로 인류의 행복과 공익성 구현을 위한 자기계발 의식과 공동체적 의식을 확장할 수 있는 교양교육내용으로 개선되어야 한다. 이에 본 연구는 W보건대학을 사례연구로 전문대학 교양교육의 개선 방향을 제시하였다는 점에 의의를 둔다. 또한 본 연구에서 제시한 4차 산업혁명시대에 따른 전문대학 교양교육의 개선 방향 세 가지는 한 대학의 사례를 넘어 국내뿐 아니라 전 세계적으로 전문대학이 기본적으로 추구해야할 공통된 방향성이다. This study aims at suggesting a direction of improvement of liberal education at junior college according to the age of the fourth industrial revolution as a research to lead the creative vocational education of the world level, among the rapid changes of super-interfusion and super-connection. As research targets, I selected 100 persons of faculty members of Wonkwang Health Science University at the first survey and selected 6 persons at the second focus group interview. As a procedure of research, I got the deliberating approval about the study plan from the Committee of Biomedical Ethics, and carried out the quantitative research as the first survey to perform a survey concerning awareness and request extent, and satisfaction degree about the liberal education, by taking as targets the faculty members of Wonkwang Health Science University. Subsequently, based on the result, I performed a qualitative research by carrying out the second focus group interview to investigate the substantial voice from within concerning the essential goal and improvement direction of liberal education that the faculty members were aware of. In consequence, I suggest the following three items for improvement direction of liberal education at the junior college according to the age of the fourth industrial revolution. First, it should be improved into liberal education for the realization of essential goals as integrated liberal education, toward the direction to connect with life beyond strengthening a basic ability to be able to possess the insight through integration and interfusion among subjects by developing excellent contents in connection with major subjects and liberal subjects. Second, it should be improved into the organic liberal education courses to be able to give various knowledges in connection with the improvement of potentials of human beings and social practice, toward the direction to be able to acquire broad discernments and understandings concerning the overall life culture including practical knowledges through the research development of liberal education courses in relation with creative and interfusing cultivation of professionals to lead the fourth industrial revolution. Third, it should be improved into the contents of liberal education that helps to be able to extend the consciousness of self-development and the community spirit, for realizing human happiness and the public interest, toward the direction to correspond to the demand of the times and society, and to strengthen the competitiveness of colleges by composing various subjects through extending practice of liberal education to utilize K-MOOC. This study has a meaning that it suggested improvement direction of liberal education at the junior college through the case research of Wonkwang Health Science University. Also, the three kinds of improvement direction of liberal education at the junior college according to the age of the fourth industrial revolution, suggested at this study, are a common direction that junior colleges should pursue basically all over the world beyond a case of one college. KCI Citation Count: 12